2013
DOI: 10.1371/journal.pone.0078482
|View full text |Cite
|
Sign up to set email alerts
|

Role of Upwelling on Larval Dispersal and Productivity of Gooseneck Barnacle Populations in the Cantabrian Sea: Management Implications

Abstract: The effect of coastal upwelling on the recruitment and connectivity of coastal marine populations has rarely been characterized to a level of detail to be included into sound fishery management strategies. The gooseneck barnacle (Pollicipes pollicipes) fishery at the Cantabrian Coast (Northern Spain) is located at the fringes of the NW Spanish Upwelling system. This fishery is being co-managed through a fine-scale, interspersed set of protected rocks where each rock receives a distinct level of protection. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Similar coexisting acclimatization of two native and invasive kelp species in the same environment has been previously evidenced, where habitat preferences were identified through specific gene expression in correlation with temperature shifts (Henkel & Hofmann, 2008). The results show that C. fragile was the predominant species during autumn sampling, whereas previously it had been predominantly found in the summer period (Rojo et al, 2014 (Rivera et al, 2013). High chlorophyll concentration levels in summer have also been observed to have a positive effect on settlement of another invasive seaweed, the Asian kelp Undaria pinnatifida along the Cantabrian coast (Báez et al, 2010).…”
Section: Factors Of Interactionssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar coexisting acclimatization of two native and invasive kelp species in the same environment has been previously evidenced, where habitat preferences were identified through specific gene expression in correlation with temperature shifts (Henkel & Hofmann, 2008). The results show that C. fragile was the predominant species during autumn sampling, whereas previously it had been predominantly found in the summer period (Rojo et al, 2014 (Rivera et al, 2013). High chlorophyll concentration levels in summer have also been observed to have a positive effect on settlement of another invasive seaweed, the Asian kelp Undaria pinnatifida along the Cantabrian coast (Báez et al, 2010).…”
Section: Factors Of Interactionssupporting
confidence: 79%
“…With the increasing temperatures along the N Spanish coast (Gómez‐Gesteira, Decastro, Alvarez, & Gómez‐Gesteira, ), a range shift in the relative abundance of seaweed species (Duarte et al, ; Voerman, Llera, & Rico, ) and the potential increase of C. fragile toward the west could be expected. Years with increased coastal upwelling at the Central Cantabrian Coast could potentially increase the seaweed distribution, as observed for the planktonic phase of local barnacle populations (Rivera et al, ). High chlorophyll concentration levels in summer have also been observed to have a positive effect on settlement of another invasive seaweed, the Asian kelp Undaria pinnatifida along the Cantabrian coast (Báez et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…Migrations and spawning behavior of adult spiny lobsters may mitigate the influence of the Agulhas Current on the downstream dispersal of larvae (Groeneveld & Branch, ; Santos, Rouillard, & Groeneveld, ), through determining the location and timing of larval release. Vertical migration of larvae in the water column has been shown to favor larval retention close to local shores (Phelps, Polton, Souza, & Robinson, ; Rivera et al, ). Teske, Sandoval‐Castillo, Sebille, Waters, and Beheregaray (), Teske, Sandoval‐Castillo, Sebille, Waters, and Beheregaray () showed that larvae can remain close to the shore and be dispersed by inshore counter‐currents.…”
Section: Discussionmentioning
confidence: 99%
“…Migrations and spawning behavior of adult spiny lobsters may mitigate the influence of the Agulhas Current on the downstream dispersal of larvae (Groeneveld & Branch, 2002;Santos, Rouillard, & Groeneveld, 2014), through determining the location and timing of larval release. Vertical migration of larvae in the water column has been shown to favor larval retention close to local shores (Phelps, Polton, Souza, & Robinson, 2015;Rivera et al, 2013 (2016) showed that larvae can remain close to the shore and be dispersed by inshore counter-currents. We suggest that P. homarus larvae can position themselves to avoid being caught up in the main Agulhas Current, and are instead dispersed by inshore counter-currents.…”
Section: Influence Of Ocean Currents On Gene Flow and Connectivitymentioning
confidence: 99%
“…Poulin et al 2002;Lagos et al 2007;Tapia et al 2009;Pfaff et al 2011;and references therein). For instance, an upwelling system in the Cantabrian Sea may not only define the spatial scale and direction of the dispersal of a gooseneck barnacle, but also the genetic structure of its metapopulation (Rivera et al 2013).…”
Section: Discussionmentioning
confidence: 99%